Chimeric RNA Oligonucleotides with Triazole and Phosphate Linkages: Synthesis and RNA Interference. Issue 12 (26th August 2015) - Fujino, Tomoko; Kogashi, Kanako; Okada, Koudai; Mattarella, Martin; Suzuki, Takeru; Yasumoto, Kenichi; Sogawa, Kazuhiro; Isobe, Hiroyuki
Abstract: Chimeric RNA oligonucleotides with an artificial triazole linker were synthesized using solution‐phase click chemistry and solid‐phase automated synthesis. Scalable synthesis methods for jointing units for the chimeric structure have been developed, and after click‐coupling of the jointing units with triazole linkers, a series of chimeric oligonucleotides was prepared by utilizing the well‐established phosphoramidite method for the elongation. The series of chimeric 21‐mer oligonucleotides that possessed the triazole linker at different strands and positions allowed for a screening study of the RNA interference to clarify the preference of the triazole modifications in small‐interfering RNA molecules. Abstract : Link by link : Chimeric RNA oligonucleotides with a triazole linker were synthesized using solution‐phase click chemistry and solid‐phase automated synthesis, which was enabled by the scalable synthesis of jointing nucleoside units. The oligonucleotides possessing the triazole linker at different strands and positions allowed for a screening study of the RNA interference to clarify the preference of the modifications.